ASPECTS REGARDING THE IMPLEMENTATION OF THE EUROPEAN ARREST WARRANT - Catalin, MARINESCU (Strategii Manageriale)
The Treaty of Amsterdam stipulated the fact that the European Union must maintain and develop an area of freedom, security and justice, freedom assuming the existence of a common judicial area in which European citizens are able to seek justice in any of the member state same as in their own country. This goal aims to eliminate the possibility that criminals exploit the differences between the legal systems of the member states, imposing that the judgments are recognized and enforced abroad without the formalities laid down by the classical conventions on international judicial assistance. The Council Framework Decision 2002/584/JHA of 13 June 2002 on the European arrest warrant and the surrender procedures between Member States, materialized the decision taken in Tampere, following that between EU Member States to be replace the formal extradition procedure of the people who evade the execution of a sentence of imprisonment imposed by a judgment of conviction became final, with a simplified surrender procedure..